2015
DOI: 10.1111/corg.12104
|View full text |Cite
|
Sign up to set email alerts
|

Managerial and Disciplinary Responses to Abandoned Acquisitions in Bidding Firms: A New Perspective

Abstract: Manuscript Type: Empirical Research Question/Issue: Existing research suggests that internal and external corporate governance mechanisms substitute for one another to mitigate agency problems in bidding firms. This paper tests whether the interaction between these mechanisms is more complementary. Research Findings/Insights: While there is evidence for disciplinary responses to bids for unrelated targets involving strategic retrenchment and significant asset divestment, the influence of the information convey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Interactions like those proposed here can be found in McCann and Ackrill (2015) works and Guo et al (2015). Even so, the findings, as mentioned earlier, may make sense for developed or emerging countries with different legal systems than the Brazilian system.…”
Section: Final Remarkssupporting
confidence: 70%
“…Interactions like those proposed here can be found in McCann and Ackrill (2015) works and Guo et al (2015). Even so, the findings, as mentioned earlier, may make sense for developed or emerging countries with different legal systems than the Brazilian system.…”
Section: Final Remarkssupporting
confidence: 70%
“…Finally, there is evidence to suggest that target firms of failed bids are more likely to be acquired over the next eight years (Malmendier et al ., 2016). Also, McCann and Ackrill (2015) find that firms abandoning a bid regarding unrelated target firms have a higher likelihood of changing their strategies related to non-core activities of the firm.…”
Section: Organizing the Themesmentioning
confidence: 89%
“…Further, targets of failed deals are more likely to be acquired following the deal failure (Malmendier et al ., 2016). It is important to understand the implications for deal completion or abandonment on the future strategies and performance of the firms (McCann and Ackrill, 2015; Weber and Camerer, 2003). Another underexplored area relates to the micro-level aspects post-deal completion especially related to turnover and restructuring of the firm.…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…Caiazza and Pozzolo, 2016; Ngo and Susnjara, 2016; Muehlfeld et al , 2012). Although a large amount of research has published on why M&A fail to create value to shareholders (announcement returns) and fail to improve accounting performance (post-merger stage) in corporate finance and strategy literatures (Asquith, 1983; Chang and Suk, 1998; De Bernardis and Giustiniano, 2015; McCann and Ackrill, 2015; Munjal and Pereira, 2015; also see reviews by Ferreira et al , 2014b; Haleblian et al , 2009; Lebedev et al , 2015; Marks and Mirvis, 2011; Martynova and Renneboog, 2008; Reddy, 2014; Shimizu et al , 2004; Yaghoubi et al , 2016), there are hardly a few empirical/survey studies that analyze abandoned deals or completion likelihood of M&A negotiations (Dikova et al , 2010; Graebner et al , 2010; Muehlfeld et al , 2007, 2012; Ngo and Susnjara, 2016; Roos and Postma, 2016; Zhang et al , 2011). In fact, some recent literature-review papers have confirmed the scant research in this particular stream – negotiation process (Ahammad et al , 2016; Caiazza and Volpe, 2015; Friedman et al , 2015; Lee et al , 2014).…”
Section: Theoretical Framework and Relevant Literaturementioning
confidence: 99%